Rancang Bangun Aplikasi Ppic Dengan Metode Abc Dalam Menentukan Penghitungan Biaya Proyek Sistem Informasi (Studi Kasus Stikom Surabaya) - Suhamto, Ardi Slamet; Sunarto, M. J. Dewiyani; Amelia, Tan (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2012)
The development of time making the development of technology is increasingly, and the need for information system becomes important. Similar to other software house, SSI prosecuted to be able to produce a quality information system at competitive rates. ABC is one of the methods used by project management information system to calculate the cost of the project. This system was built to help the project costing information system. The estimated cost is used as the control over project execution. This system is also built to help control and project management information system. From the implementation and evaluation has been done, the system has been created, can able to calculate the estimated cost of the project, using the ABC method. The system is also able to manage the project Keywords: Information System, ABC, Project Management